Social Theory & Health - Scambler, Graham; Higgs, Paul.; Graham, Ruth.; Levinson, Richard; Giarelli, Guido; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan.)
Social Theory & Health provides an international scholarly forum for theoretical reflection and debate on contemporary health issues, many of which bear directly on the planning and delivery of services. The journal aims to consolidate, refine and extend theoretically informed work on the role of health in modern societies. Interest in issues of theory and health now informs many academic and practice-oriented disciplines and crosses discipline boundaries. The Editors encourage contributions from all relevant disciplines, as well as from those involved directly in front-line treatment and care. Contributions from the developing world are particularly welcome. The journal aims to include contributions from all theoretical perspectives.
Keywords: Social sciences; Sociology; Social sciences -- Philosophy; Social medicine; Social Sciences, general; Sociology, general; Medical Sociology; Social Theory